2013
DOI: 10.3390/metabo3040931
|View full text |Cite
|
Sign up to set email alerts
|

The Complex Role of Branched Chain Amino Acids in Diabetes and Cancer

Abstract: The obesity and diabetes epidemics are continuing to spread across the globe. There is increasing evidence that diabetes leads to a significantly higher risk for certain types of cancer. Both diabetes and cancer are characterized by severe metabolic perturbations and the branched chain amino acids (BCAAs) appear to play a significant role in both of these diseases. These essential amino acids participate in a wide variety of metabolic pathways, but it is now recognized that they are also critical regulators of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
103
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(117 citation statements)
references
References 79 publications
12
103
0
2
Order By: Relevance
“…They account for approximately one-third of the essential amino acids in muscle proteins and nearly 40% of the preformed amino acids required by mammals (6). These amino acids have unique chemical structures, including aliphatic side chains with a branch, which is why the BCAAs are named so (7).…”
Section: Introductionmentioning
confidence: 99%
“…They account for approximately one-third of the essential amino acids in muscle proteins and nearly 40% of the preformed amino acids required by mammals (6). These amino acids have unique chemical structures, including aliphatic side chains with a branch, which is why the BCAAs are named so (7).…”
Section: Introductionmentioning
confidence: 99%
“…Different hypotheses are discussed regarding the positive associations between BCAA and obesity as well as IR, for example, BCAA effects on the m-TOR pathway [58] . BCAA may activate m-TOR and cause IR in obese people.…”
Section: Childhoodmentioning
confidence: 99%
“…25,26 The increased plasma BCAA concentration may be the result of the impaired BCAA-catabolizing capacity of the adipose tissue, an improper high-fat and highprotein diet (dietary protein comprised of >20% BCAA) and increased catabolic pathways of BCAAs. 13,20,27,28 So far, only a few studies rated the changes in the BCAA levels after weight loss through diet and physical activity, but those studies were conducted on different populations (especially Caucasian and Japanese subjects) and used another model of body mass reduction program (based on nutritional recommendation and lifestyle intervention, but not a strictly composed diet). A 7-year prospective KORA study on a group of Caucasian patients with obesity showed a significant correlation between the average percentage increase in body weight and the increase in the BCAA, phenylalanine, tyrosine, and glutamate levels.…”
Section: Discussionmentioning
confidence: 99%